A structured curriculum and procedure clinic to help family medicine residents diagnose and treat skin cancer - Rivet, Christine; Motamedi, Farhad; Burns, Joseph; Archibald, Douglas (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Melanoma is a potentially deadly type of skin cancer that has been increasing in incidence but is curable if found in the early stages. Family physicians are in an ideal situation to examine the skin during routine visits, but studies indicate they are not well trained to detect or treat skin cancers. We piloted a structured, longitudinal, hands-on procedural curriculum to improve family medicine residents’ ability to identify and manage skin cancers. Family medicine residency programs wishing to improve the diagnosis and management of skin cancer by family physicians might consider trialing our structured curriculum and procedure clinic.